Ouvriers molenbeekois : les immigrés marocains - Massange, Catherine; Van Wuytswinkel, Jan; Sabiliki, Nelly; Ceustermans, Claudette (Les Cahiers de la Fonderie : revue d'histoire sociale et industrielle de la région bruxelloise)
"Has Abdelkader Hichou, Ben Ahmed Assri, Khadday Hichou Assri, Mohamed El Mokrani Entretiens"